The Holy, Non-Christic Biblical Subtexts in Superman: The Movie (1978) and Superman II (1981) - Kozlovic, Anton K. (The journal of religion and film, 2002)
The sacred-secular parallels between Jesus Christ and Kal-El/Clark Kent/Superman in Superman: The Movie (1978) and Superman II (1981) were explicated previously in JR&F. Despite the persuasive Christic subtext, the richness of the biblical parallels within these two SF films did not stop with just an alien Messiah. Further engineered biblical correspondences existed that complemented the Christic subtext and uprated the overall sanctity of the filmic narratives. Three areas of holy infranarratives were identified and explicated pertaining to: (a) divine figurations, (b) blessed parents, and (c) holy associates. Further research into this exciting field was recommended.